3r(5r-3)=0

Divide each term in 3r(5r-3)=0 by 3.

3r(5r-3)3=03

Cancel the common factor.

3r(5r-3)3=03

Divide r(5r-3) by 1.

r(5r-3)=03

r(5r-3)=03

Divide 0 by 3.

r(5r-3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

r=0

5r-3=0

Set the first factor equal to 0.

r=0

Set the next factor equal to 0.

5r-3=0

Add 3 to both sides of the equation.

5r=3

Divide each term by 5 and simplify.

Divide each term in 5r=3 by 5.

5r5=35

Cancel the common factor of 5.

Cancel the common factor.

5r5=35

Divide r by 1.

r=35

r=35

r=35

r=35

The final solution is all the values that make 3r(5r-3)3=03 true.

r=0,35

Solve using the Square Root Property 3r(5r-3)=0